Post-Graduate Perceptions On Online Subject Registration - A Case Study At UiTM / Farah Adlina Ropaie...[et al.] - Ropaie, Farah Adlina; Abdul Razak, Razita; Arshad, Hidayati; Ahmad, Jasmine (2010)
This study identifies the perceptions of post-graduate students on the ease of use and usefulness of the online subject registration. Online subject registration for post-graduate students was first introduced and implemented in July 2007 which is in line with UiTM's vision to become world class university. The objective of the online registration system is to ensure registration is made easier and faster to meet the user requirement. In the online system, data is entered into a device, such as a terminal, that is connected directly to a computer. The user will then interact with the computer through a terminal. Though the objective of the system is to encourage an easier and efficient registration system, there are factors discouraging the students from using the online registration system such as system congestions, unfriendly user tools, non-IT literates, and individual attitudes toward the technology. Self administered questionnaires were distributed among post-graduate students in various faculties. These findings are significant in understanding the constraint from the customer's perception and thus upgrading the level of online service performance by UiTM, Shah Alam.